Davek na nepremičnine v Sloveniji - Mitrović, Dušan (Geodetski vestnik, 1998)
The paper presents the existing situation in the field of property appraisal and tax essessment in Slovenia, with a description of its institutional, organizational, content and technological regulation on the basis of available data, legislation and regulations
Keywords: davki; nepremičnine; organizacija; Slovenija; vrednotenje